Numerical Modeling of Tsunami Waves Interaction with Porous and Impermeable Vertical Barriers - Manuel del Jesus; Javier L. Lara; Inigo J. Losada (Journal of Applied Mathematics)
Tsunami wave interaction with coastal regions is responsible for very important human and economic losses. In order to properly design coastal defenses against these natural catastrophes, new numerical models need to be developed that complement existing laboratory measurements and field data. The use of numerical models based on the Navier-Stokes equations appears as a reasonable approach due to their ability to evaluate complex flow patterns around coastal structures without the inherent limitations of the classical depth-averaged models. In the present study, a Navier-Stokes-based model, IH-3VOF, is applied to study the interaction of tsunami waves with porous and impermeable structures. IH-3VOF is able to simulate wave flow within the porous structures by means of the volume-averaged Reynolds-averaged Navier-Stokes (VARANS) equations. The equations solved by the model and their numerical implementation are presented here. A numerical analysis of the interaction of a tsunami wave with both an impermeable and porous vertical breakwater is carried out. The wave-induced three-dimensional wave pattern is analysed from the simulations. The role paid by the porous media is also investigated. Finally, flow around the breakwater is analyzed identifying different flow behaviors in the vicinity of the breakwater and in the far field of the structure.